ASESMEN BAKAT DAN MINAT UNTUK MENENTUKAN POTENSI KARIR SISWA DI SDN CARINGIN NUNGGAL DAN SDN MALEBER GARUT JAWA BARAT - Basaria, Debora; , Zamralita; Fahlevi, Reza; Widyastuti, Philomena Esti (Jurnal Bakti Masyarakat Indonesia, 2025)
Equitable and quality education is the main foundation in shaping a young generation that is ready to face future changes and challenges. However, before children are directed towards a particular educational or career path, it is important for them to first recognize themselves—including their strengths, interests, and character. Based on this idea, the Faculty of Psychology at Tarumanagara University, together with KKN students, conducted psychological assessments for sixth-grade students at SDN Caringin Nunggal and SDN Maleber on February 27, 2025. This activity was attended by 36 students using three instruments, namely Colored Progressive Matrices (CPM) to assess cognitive abilities, Self-Directed Search (SDS) Holland to explore career interests, and ENS_48 to map personalities. The assessment results showed that nearly half of the students had excellent cognitive abilities. In terms of interests, many students showed a tendency toward social, artistic, and investigative fields, which emphasize interaction, creativity, and curiosity. Meanwhile, the prominent personality traits were warmth and openness, as reflected in high scores on the agreeableness and openness dimensions. These results are expected to serve as a starting point for students to understand themselves more deeply. With the support of teachers and parents, this assessment plays an important role as a guide in designing educational steps and futures in line with the potential of each child.   ABSTRAKPendidikan yang merata dan berkualitas merupakan pondasi utama dalam membentuk generasi muda yang siap menghadapi perubahan dan tantangan masa depan. Namun, sebelum anak diarahkan pada jalur pendidikan maupun karier tertentu, penting bagi mereka untuk mengenali diri terlebih dahulu—meliputi kekuatan, minat, dan karakter yang dimiliki. Atas dasar pemikiran tersebut, Fakultas Psikologi Universitas Tarumanagara bersama mahasiswa KKN menyelenggarakan asesmen psikologi bagi siswa kelas VI di SDN Caringin Nunggal dan SDN Maleber pada 27 Februari 2025. Kegiatan ini diikuti oleh 36 siswa dengan menggunakan tiga instrumen, yaitu Coloured Progressive Matrices (CPM) untuk menilai kemampuan kognitif, Self-Directed Search (SDS) Holland untuk mengeksplorasi minat karier, serta ENS_48 untuk memetakan kepribadian. Hasil asesmen memperlihatkan bahwa hampir separuh siswa memiliki kemampuan kognitif pada kategori sangat baik. Dari sisi minat, banyak siswa menunjukkan kecenderungan pada bidang sosial, artistik, dan investigatif, yang menekankan interaksi, kreativitas, serta rasa ingin tahu. Sementara itu, kepribadian yang menonjol adalah sifat hangat dan terbuka, tercermin dari skor tinggi pada dimensi agreeableness dan openness.Hasil ini diharapkan dapat menjadi pijakan awal bagi siswa untuk memahami diri secara lebih mendalam. Dengan dukungan guru dan orang tua, asesmen ini berperan penting sebagai panduan dalam merancang langkah pendidikan dan masa depan sesuai potensi yang dimiliki anak.